Empowerment Of Fermented Kitchen Waste To Improve The Economy Of The Sei Mencirim Village Community And Sell Processed Products Through Internet Technology - Errie Margery; Wan Suryani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Sei Mencirim village is a village consisting of various tribes who come from several areas in North Sumatra. Sei Mencirim Village consists of 24 hamlets.The Sei Mencirim Village Community Work consists of groups that do not work as much as11,72%, groups that take care of the household as much as 25 %,groups of students as much as 30, 38 %, groups of retirees as much as 0,24%, groups of farmers 1,46%. The total population of the Sei Village community is 8608 population consisting of 4052 male population and 4556 female population. At present the role of the state apparatus in protecting the community is quite dependent on their income from work and farming and for those whose income is uncertain therefore one of the easiest product manufacturing modalities to find is to utilize household waste. Household waste is one factor that needs to be addressed. From household waste management, it can be used as a product that has economic value. An alternative to waste management is to deal with the problem thourghly and sustainably by recycling waste into eco enzyme, which come from organic waste, namely leftover vegetables and fruits. Therefore, by looking at the group of housewives as much as 25 %, recycling waste management can support the economy of housewives in Sei Mencirim Village as additional income.The service team decided to hold socialization in the hope that the community, especially the housewives of Sei Mencirim Village, could change their mindset and advance their village in their own way and style. This community service activity for the people of Sei Mencirim Village provides understanding to the community to mange household waste into products that have economic value and support the economy for the people of Sei Mencirim Village, especially for housewives and has an impact on environmental cleanliness.